La evasión de procedimientos de contratación pública como peculado: una lectura crítica del derecho penal garantista (Sección Abierta) - León González, Pablo Andrés (2026)
The reform of article 278 of the Ecuadorian Criminal Code (COIP), which incorporates the evasion of public procurement procedures as a modality of the crime of embezzlement, has sparked a significant debate regarding its scope and interpretation. This analysis is particularly relevant due to its implications for legal certainty and core principles such as proportionality and the principle of minimal criminal intervention. The objective of this study is to critically examine the possible interpretations of this provision— whether as an aggravating factor, as an autonomous offense, or as a modality dependent on the base type of embezzlement—and to propose a reading consistent with the principles of a rights-based criminal law. The study concludes that the most coherent interpretation is the one that subsumes the evasion of procurement procedures under the base type of embezzlement, requiring the presence of all its essential elements, such as personal or third-party benefit and the misuse of public resources. Criminalizing the mere breach of formal procedures, absent any patrimonial harm or illegitimate benefit, constitutes a disproportionate expansion of criminal law that risks penalizing administrative actions lacking real criminal relevance. This expansive approach undermines legal certainty and the guarantees inherent to the rule of law. The research was conducted using a qualitative, dogmatic-legal methodology.